The role of identity capitals in the success of the transition to post-sport life : a longitudial case study of a young professional footballer - Liimatta, Julius (2024)
In the case of young athletes, a sports-oriented environment often strongly encourages sports, which may limit their exploration of non-sports-related dreams and career paths outside of sports. A strong athletic identity increases the risk of psychological distress at the end of a professional sports career.